Aura: la novela fantástica del autor Carlos Fuentes - DINIZ, Poliana Serrão (2021)
This objective work makes an analysis of the work, Aura (1962) by Mexican author Carlos Fuentes, based on the fantastic aspect. In this way, the analytical corpus of this research will be the edition of the year (2001) reprinted by the Era library, having fifty pages, of a tangle in which characteristic elements of the fantastic literature of the eighteenth and twentieth centuries arise, when I had its emergence and development in various countries. On the other hand, recognizing the breadth of that genre this research was delimited in the following three themes: supernatural and ideal love, time in contrast to youth and old age, in addition to the myth of double. In that aspect the approach is qualitative and includes theories about the fantastic literature of Bento (2019), Todorov (1981). In addition to the studies on the novel Aura de Aguirre (2015) Mattei (1990) Sánchez (2008), Tamayo (2014), as well as the approach of the theme of the double with the postulates of Herrero (2011) and López (2006) and various other authors who will contribute to this theoretical analysis study. So, through this research I wanted to show the presence of the fantastic in Fuentes's novel. So the fantasy is also a narrative genre that proposes to reflect expressly in literature and also in society.